Aircraft Stories : Decentering the Object in Technoscience - Law, John, 1946- (Book collections on Project MUSE., 2002)
In Aircraft Stories noted sociologist of technoscience John Law tells stories about a British attempt to build a military aircraft-the TSR2. The intertwining of these stories demonstrates the ways in which particular technological projects can be understood in a world of complex contexts. Law works to upset the binary between the modernist concept of knowledge, subjects, and objects as having centered and concrete essences and the postmodernist notion that all is fragmented and centerless. The structure and content of Aircraft Stories reflect Law's contention that knowledge, subjects, and particularly objects are fractionally coherent: that is, they are drawn together without necessarily being centered. In studying the process of this particular aircraft's design, construction, and eventual cancellation, Law develops a range of metaphors to describe both its fractional character and the ways its various aspects interact with each other. Offering numerous insights into the way we theorize the working of systems, he explores the overlaps between singularity and multiplicity and reveals rich new meaning in such concepts as oscillation, interference, fractionality, and rhizomatic networks. The methodology and insights of Aircraft Stories will be invaluable to students in science and technology studies and will engage others who are interested in the ways that contemporary paradigms have limited our ability to see objects in their true complexity.--